Breast cancer stem cells - Owens, Thomas W.; Naylor, Matthew J. (Frontiers in Physiology, 2013)
Cancer metastasis, resistance to therapies and disease recurrence are significant hurdles to successful treatment of breast cancer. Identifying mechanisms by which cancer spreads, survives treatment regimes and regenerates more aggressive tumours are critical to improving patient survival. Substantial evidence gathered over the last 10 years suggests that breast cancer progression and recurrence is supported by cancer stem cells (CSCs). Understanding how CSCs form and how they contribute to the pathology of breast cancer will greatly aid the pursuit of novel therapies targeted at eliminating these cells. This review will summarise what is currently known about the origins of breast CSCs, their role in disease progression and ways in which they may be targeted therapeutically.